Cognitive Behavioral Counseling with Modelling Pan Balang Tamak to Improve Persuasive - Komang Adi Cipta Ananda; I Ketut Dharsana; Ni Ketut Suarni (Bisma The Journal of Counseling, 2017)
This study aimed to determine the effect of cognitive behavioral counseling by modeling techniques Pan balang greedy to increased interest persuasive students through lesson study VIII.4 grade students of SMP Negeri 2 Singaraja. This research is the study design "quasi-experimental (Quasi Experiment)" Design nonequivalent pretest-posttest control group design. The sampling technique used is random sampling and random class as an intact group of subjects of this study were 38 people VIII.4 grade students of SMP Negeri 2 Singaraja. The process of taking data in this study using the method of observation, interviews, diaries and questionnaires Interests linkert scale pattern persuasive and descriptive analysis and statistical analysis used the formula for the t-test. Empirical findings in this study stated that there are significant cognitive-behavioral counseling by modeling techniques Pan balang greedy to increased interest persuasive students through lesson study VIII.4 grade students of SMP Negeri 2 Singaraja. This is evidenced by the t value of 3,516 sig.0,01 with 0:01 <0.05. with a significance level (p) <0.05 indicating that counseling services will be more effective if counselees in the implementation of the service is facilitated by modeling techniques Balang Greed Pan models. Based on this statement we can say that the cognitive-behavioral counseling by modeling techniques Balang Greed Pan right models applied in schools.